EXAFS investigation of the role of Cu on the chemical order and lattice distortion in L10 Fe–Pt–Cu thin films. (1st October 2014) - Laureti, S.; Brombacher, C.; Makarov, D.; Albrecht, M.; Peddis, D.; Varvaro, G.; D'Acapito, F.
<x xml:space="preserve">Abstract</x> This work presents an extended X‐ray absorption fine structure (EXAFS) characterization of ternary Fe–Pt–Cu alloys with different Cu content. The EXAFS measurements have been carried out at the Cu Kα and Pt LIII edges in order to describe the local environment around these elements in the Fe–Pt–Cu samples and to compare the structural evolution as a function of the Cu content. The EXAFS study, based on a substitutional model where the Cu atoms occupy Fe or Pt sites in the tetragonal structure, has been performed by using linear dichroism to enhance the sensitivity to differently oriented bonds and to gain a detailed description of the atomic environment. The study allowed the effects on the chemical order and lattice distortion induced by the Cu atoms to be distinguished experimentally. The determined positions of the Cu atoms in the chemically L10‐ordered face‐centred tetragonal lattice were correlated with the magnetic properties of Fe–Pt–Cu ternary alloys. In particular, the main effect of Cu atoms in the alloy is a linear reduction of the c/a ratio, while the nonmonotonic behaviour of the chemical order is consistent with the variation of the magnetocrystalline anisotropy.